Improvements in the World Bank’s Ease of Doing Business Rankings : Do they Translate into Greater Foreign Direct Investment Inflows? - Jayasuriya, Dinuk (2012)
The World Bank's Ease of Doing Business reports have been ranking countries since 2006. However, do improvements in rankings generate greater foreign direct investment inflows? This study is the first to test such a proposition empirically with Arellano-Bond dynamic panel estimators using the official rankings from 2006 to 2009. The paper shows this relationship is significant for the average country. However, when the sample is restricted to developing countries, the results suggest an improved ranking has, on average, an insignificant (albeit positive) influence on foreign direct investment inflows. Although robust, this result should be taken with caution given that it refers to the average developing country using data across a four-year time period. Finally, the paper demonstrates that, on average, countries that undertake large-scale reforms relative to other countries do not necessarily attract greater foreign direct investment inflows. This analysis may have important ramifications for developing country governments wanting to improve their Doing Business Rankings in the hope of attracting foreign direct investment inflows.